Free fall - Mehl, Nancy (Mehl, Nancy. Quantico files, 2022)
"When dark-haired women across Virginia begin to suddenly disappear, FBI behavioral analyst Alex Donovan is tasked with hunting the kidnapper down. But when Alex herself is baited and abducted at an abandoned amusement park, her partner Logan Hart and the BAU team fear Alex might not make it out alive this time"--